Lifelong learning in the UK : an introductory guide for education studies - O'Grady, Anne (Educator) (London ; New York : Routledge, 2013)
"Written specifically for Education Studies students, this accessible text offers a clear introduction to lifelong learning and the impact it has on all areas of society. Assuming no prior knowledge of the subject, it explores what lifelong learning is, where learning can and does take place and who is accessing it. Offering a clear overview of the different strands to lifelong learning, the book examines the concept of lifelong learning drawing on key policy initiatives and strategies. Each section outlines the types of individuals who are most likely to access lifelong learning within and across these strands including, for example, migrants, refugees and asylum seekers, unemployed adults, carers and guardians, older age-groups and returning learners. Chapters cover: - adult and community learning; - higher education; - further education; - work-based learning; - prison and probation learning. Including supporting tasks and reflection activities, this textbook will give students a broad understanding of lifelong learning and its role in supporting adults throughout their life both socially and economically. Lifelong Learning in the UK is an essential introductory text for students on undergraduate courses in Education Studies"--
Includes bibliographical references and index.
Description based on metadata supplied by the publisher and other sources.
Electronic reproduction. Santa Fe, Arg.: elibro, 2020. Available via World Wide Web. Access may be limited to eLibro affiliated libraries.
Keywords: Continuing education -- Great Britain; Adult education -- Great Britain; Electronic books